New methods for electrochemical determination of pesticides (a review) - Fischer, Jan; Barek, Jiri; Wang, Joseph (Univerzita Pardubice, 2012)
The review briefly summarizes the present situation in the field of electroanalytical determination of various types of pesticides. It is focused on papers published in years 2010 – – 2012 with special emphasis on methods developed in UNESCO Laboratory of environmental electrochemistry in Prague in the framework of the Czech – American S&T Cooperation in association with the laboratory of Joseph Wang, Department of Nanoengineering, University of California, San Diego, based on project NEMVAD (New electrode materials for voltammetric and amperometric detection) supported by AMVIS (American Science Information Center) in Prague and by Ministry of Education, Youth and Sports of the Czech Republic.
Keywords: pesticides; voltammetry; amperometry; sensors; electrodes; supramolecular chemistry